Elucidation of the Molecular Mechanism and Exploration of Novel Therapeutics for Spinocerebellar Ataxia Caused by Mutant Protein Kinase Cγ - Takahiro Seki; Naoko Adachi; Nana Abe-Seki; Takayuki Shimahara; Hideyuki Takahashi; Kazuhiro Yamamoto; Naoaki Saito; Norio Sakai (Elsevier, 2011)
Abstract.: Spinocerebellar ataxia (SCA) is an inherited neurodegenerative disorder that is characterized by cerebellar atrophy and progressive ataxia and is classified into 31 types by the genetic locus. Recently, missense mutations of PRKCG genes that code protein kinase Cγ (γPKC) have been identified as a causal gene of SCA14. To explore the molecular mechanism of SCA14 pathogenesis, we investigated how mutant γPKC causes the neurodegeneration of cerebellar Purkinje cells (PCs) by expressing mutant γPKC-GFP in cell lines and primary cultured PCs. Mutant γPKC was susceptible to aggregation in the cytoplasm, which led to an impairment of the ubiquitin-proteasome system and apoptosis. Furthermore, mutant γPKC induced improper dendritic development of cultured PCs in an aggregation-independent manner. Stimulation-induced translocation of mutant γPKC in PC dendrites was prominently attenuated by the reduced mobility of oligomerized mutant γPKC, which resulted in attenuated signal transduction and the improper morphology of PC dendrites. These findings suggested that the oligomerization and aggregation of mutant γPKC caused improper dendritic development and apoptosis of PCs, which led to cerebellar dysfunction and SCA14 pathogenesis. We screened the chemicals that improved these cellular dysfunctions and identified several compounds, including trehalose and Congo red, which could be novel therapeutics for SCA14. Keywords:: spinocerebellar ataxia, protein kinase Cγ, cerebellar Purkinje cell aggregation, apoptosis